A Comparative Study of Formative Assessment in Medicine Using Conventional Long Case Examination and Objective Structured Long Examination Record (OSLER) Among Final Year MBBS Students (Academia Journal of Medicine, 2019)
Background: Most medical colleges in India traditionally use the Long Case Examination (LCE) in both formative and summative patterns of  assessment in clinic. This age-old issue has been addressed over the years by the introduction of several modifications of the LCE such as  OSCE and OSLER. OSCE, though attractive in its brevity and specificity of focus, falls short in terms of being comprehensive. This study was  taken up to compare conventional LCE to OSCE and OSLER. Subjects and Methods: Final year MBBS students, posted to Department of  General Medicine, HIMS, Hassan were studied for 5 months. Type of study: Prospective observational study Four examiners were selected for  the formative assessment: Examiners 1 and 2 were asked to assess the students assigned to Group 1; Examiners 3 and 4 were asked to assess  Group 2. The OSLER method concentrates on the following ten items: (1) pace and clarity of presentation, (2) communication process, (3)  systematic approach, (4) Establishment of case facts, (5) systematic examination, (6) Examination technique, (7) Establishment of correct  physical findings. Results: The mean time taken for the assessment in Group 1 was 28.22 minutes and the SD was 7.588. The mean time taken  for the assessment in Group 2 was 17.09 minutes and the SD was 4.546. Conclusion: In our study, the students seem to prefer the time-tested  long case examination and did score better marks with the conventional method than with OSLER.
Keywords: Long Case Examination; OSLER; OSCE